Teacher's Efforts in Overcoming Student’s Difficulty Post Distance Learning at Elementary School - Tutut Handayani; Masnun Baiti; Ayu Nur Shawmi; Ines Tasya Jadidah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The aim of this research is to analyze teachers' efforts to overcome students' learning difficulties after distance learning in elementary schools. This study used qualitative research methods. The subjects in this research were the principal, teachers and students in grades 3, 4 and 5 at the Al Fahd Islamic elementary school in Palembang. The data collection techniques used were interviews, observation, documentation, Focus Group Discussions (FGD), and questionnaires in the form of open and closed questions via Google Form. Data was analyzed using an interactive model, namely data condensation, data presentation and conclusions. Data validity testing was carried out by data triangulation. The results of the research show that the teacher's efforts in overcoming students' learning difficulties, first the teacher takes a direct approach to students such as direct and persuasive attention, guidance and direction to students, provides opportunities for students to speak/express opinions, answer questions, and writing opinions in front of the class, providing encouragement or motivation to students, and giving praise and rewards to students. Second, teachers apply effective and enjoyable strategies/models/and methods and learning such as active learning, question and answer, discussion/group study, contextual learning, inquiry (observation), direct experimentation, Problem-Based Learning (PBL), and Project Based Learning (PJBL). Third, teachers use learning media, Learning Videos via LCD projector, Power Point, and experimental media. Fourth, collaboration with parents. Collaboration between the school, especially teachers, and parents of students is deliberately programmed from the start before learning begins (parents meeting). These efforts have an impact on the students' learning process. Students feel happy participating in learning.